2012
DOI: 10.1039/c1nr10911a
|View full text |Cite
|
Sign up to set email alerts
|

Smart cleaning of cultural heritage: a new challenge for soft nanoscience

Abstract: The search for innovative, smart and performing cleaning agents is one of the main issues of modern conservation science. Nanosciences do not only provide solutions to this scientific field in terms of new materials but also change radically the approach to problems and challenges. In this feature article we review the most innovative nanostructured systems developed in the last decade for the cleaning of artworks together with some noteworthy case studies. Micelles, microemulsions, thickened complex fluids, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 54 publications
1
82
0
4
Order By: Relevance
“…In EAPC the solvents are partitioned between the continuous phase and the dispersed droplets (PEA = 0.7; PPC = 0.3; PPeOH = 0.9). EAPC has faster removal kinetics than XYL towards the same acrylate copolymer (Paraloid® B72, ethyl methacrylate/methyl acrylate [14] and can be considered as one of the most performing systems, as it could remove a multi-layered coating of degraded polymers from the surface of wall paintings in the Annunciation Basilica in Nazareth, Israel (see Figure 2), where both traditional solvents and the XYL system had proven ineffective. Insights in the removal mechanisms have been provided along with structural studies, distinguishing between two different cases: 1) interaction of o/w fluids with low molecular weight compounds (fatty acids and triglycerides found in grime); 2) interaction with polymers, e.g.…”
Section: Microemulsions and Micellesmentioning
confidence: 99%
See 3 more Smart Citations
“…In EAPC the solvents are partitioned between the continuous phase and the dispersed droplets (PEA = 0.7; PPC = 0.3; PPeOH = 0.9). EAPC has faster removal kinetics than XYL towards the same acrylate copolymer (Paraloid® B72, ethyl methacrylate/methyl acrylate [14] and can be considered as one of the most performing systems, as it could remove a multi-layered coating of degraded polymers from the surface of wall paintings in the Annunciation Basilica in Nazareth, Israel (see Figure 2), where both traditional solvents and the XYL system had proven ineffective. Insights in the removal mechanisms have been provided along with structural studies, distinguishing between two different cases: 1) interaction of o/w fluids with low molecular weight compounds (fatty acids and triglycerides found in grime); 2) interaction with polymers, e.g.…”
Section: Microemulsions and Micellesmentioning
confidence: 99%
“…These observations were combined with analysis of both the fluids and the polymer film through Differential Thermogravimetry (DTG), Small-Angle X-ray Scattering (SAXS), Quasi-Elastic Light Scattering (QELS), SANS, and Atomic Force Microscopy (AFM). [14,15] It was shown that EAPC interacts with the polymer through a multi-step mechanism: 1) the swollen micelles act as reservoirs that exchange solvents with the polymer film; 2) the polymer selectively extracts an optimal solvent composition from the micelles; 3) the coating swells because of solvent diffusion into the polymer network (probably following case II diffusion [16] ) and detaches from the substrate, while the micelles get smaller and re-organize their structure after solvent exchange. The cosurfactant (1-PeOH) has a double role in XYL, as it builds the droplets and enhances the polymer removal.…”
Section: Accepted Manuscript Angewandte Chemie International Editionmentioning
confidence: 99%
See 2 more Smart Citations
“…), and their low solvent content reduces the environmental impact. In fact, throughout the last decade, nanostructured fluids have been widely tested for the cleaning of mural paintings, and the results obtained have demonstrated that these systems are a valid alternative to the use of neat solvents [8][9][10][11]. However, for their use on watersensitive substrates, o/w microemulsions must be confined within a retentive network that allows their controlled release, so as to grant the removal of unwanted layers without excessive wetting of the surface.…”
Section: Introductionmentioning
confidence: 99%